ROLE OF DOUBLE INSEMINATION TO IMPROVE THE CONCEPTION RATE IN REPEAT BREEDING GRADED BUFFALOES - Vijayarajan, A; Chandrahasan, C; Napolean, R Ezakial (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Twenty repeat breeding, pluriparous, graded buffaloes were equally divided into two groups as group I (control) and II (double AI). Group I served as control and were inseminated at mid heat during natural estrus. Group II were inseminated twice at an interval of 12 hours during the same estrus period. No difference was observed between single and double AI groups with respect to the conception rate.